Chemical modification of ovatodiolide revealed a promising amino-prodrug with improved pharmacokinetic profile. Issue 75 (28th August 2020) - Xiang, Junhong; Zhang, Xuemei; Wang, Dehong; Li, Jiaxin; Li, Qiuying; Wang, Qin; Ding, Yahui; Chen, Tianyang; Sun, Yuanjun; Bao, Shiqi; Chen, Jing; Li, Dongmei; et al.
Abstract : Stepwise modification of ovatodiolide revealed a prodrug NMP-diepoxyovatodiolide, which is a very promising candidate for further development of liver-related drugs. Abstract : Stepwise modification of ovatodiolide revealed a prodrug, NMP-diepoxyovatodiolide, which can provide sustained release of an active compound, substantial metabolic stability and a unique accumulation profile in the liver. Besides, NMP-diepoxyovatodiolide demonstrated therapeutic benefits in an acute autoimmune hepatitis mouse model and a broad safety window. Therefore, NMP-diepoxyovatodiolide is a very promising candidate for further development of liver-related drugs.